2021
DOI: 10.4067/s0717-95022021000100260
|View full text |Cite
|
Sign up to set email alerts
|

Isokinetic Strength, Bilateral and Unilateral Strength Differences: Variation by Age and Laterality in Elite Youth Football Players

Abstract: The purpose of this study was to investigate the effect of age on peak torque (PT) relative strength measures of knee extensors (KE) and knee flexors (KF), bilateral strength ratio (Q:Q, H:H), and ipsilateral strength ratio (H:Q) in youth elite male football players.Elite male players (n = 70) from four age categories (U16: n = 20, U17: n = 20, U19: n = 15, U21: n = 15) performed isokinetic strength tests using a Cybex dynamometer. Results show a significant effect of age on PTKE (F3,142 = 4.54, p = 0.005, = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…The main finding of our study was the significant (p < 0.05) effect of the AC on the prevalence of BA in KEs and KFs among the analyzed categories (U13, U15, and U17). However, the study by Maly et al [17] did not confirm this finding in their analysis of the U16-U21 categories. The study presented lower BA average values (Q:Q = 7.97-9.29%, H:H = 7.94-11.47%) than those in our study (Q:Q = 6.29-11.10%, H:H = 7.79-12.12%), suggesting that longer playing and training durations improve the neuromuscular environment; thus, athletes become more resilient and BA appears to be stabilized [25].…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The main finding of our study was the significant (p < 0.05) effect of the AC on the prevalence of BA in KEs and KFs among the analyzed categories (U13, U15, and U17). However, the study by Maly et al [17] did not confirm this finding in their analysis of the U16-U21 categories. The study presented lower BA average values (Q:Q = 7.97-9.29%, H:H = 7.94-11.47%) than those in our study (Q:Q = 6.29-11.10%, H:H = 7.79-12.12%), suggesting that longer playing and training durations improve the neuromuscular environment; thus, athletes become more resilient and BA appears to be stabilized [25].…”
Section: Discussionmentioning
confidence: 79%
“…One possible reason is the reduced ability to cope with pre-existing asymmetries from incomplete maturation of their kinetic and neuromuscular patterns. Contrastingly, Maly et al [17] did not confirm a significant effect of age on BA level, although they presented higher average values of BA in KEs and knee KFs in the older categories (U19 and U21) than in the younger categories (U16 and U17).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Limb preference is the preferred leg (PL) while kicking a ball, according to one definition. 29 During the 2021–2022 season, all competitors played in the First Portuguese League.…”
Section: Methodsmentioning
confidence: 99%
“…They can manifest in aspects ranging from gait mechanics to the change of direction differences (Nicholson et al, 2022). However, the largest BLA in soccer has been reported in lower limb strength (Nicholson et al, 2022), with this being affected by long-standing participation in soccer (Fousekis et al, 2010b;Maloney, 2019;Maly et al, 2021). Côté et al (2007) reported that elite players achieved more hours in specific football training during childhood and adolescence compared to those who did not achieve professional status.…”
Section: Introductionmentioning
confidence: 99%